Farm size and income distribution of Latin American agriculture: New perspectives on an old issue - Margarita Gáfaro; Ana María Ibá\~nez; Daniel Sánchez-Ordó\~nez; María Camila Ortiz (Inter-American Development Bank (IDB), 2023)
Latin American and Caribbean countries have historically been known for their rates of land inequality, highest in the world. However, these countries also exhibit a high degree of heterogeneity in their patterns of land concentration and average farm sizes. These cross-country differences play a determining role in productivity of farms and the distribution of agricultural income. Constructing a new data-set matching agricultural census and household survey data, we provide suggestive evidence on the positive relationship between farm size and farm income and wages. We identify the prevalence of small farms and the resulting low agricultural incomes as an important mechanism contributing to high income inequality in agricultural regions. Low labor productivity in small farms appears as a key explanatory factor.
Keywords: O13; O15; O54; J43; Q12; Q15; 330; Land inequality; Productivity; Agricultural income